Angelica gigas Nakai Has Synergetic Effects on Doxorubicin-Induced Apoptosis. (1st August 2018) - Jeon, Yong-Joon; Shin, Jong-Il; Lee, Sol; Lee, Yoon Gyeong; Kim, Ji Beom; Kwon, Hak Cheol; Kim, Sung Hun; Kim, Inki; Lee, Kyungho; Han, Ye Sun
Abstract : Natural products are valuable sources for drug discovery because they have a wide variety of useful chemical components and biological properties. A quick reevaluation of the potential therapeutic properties of established natural products was made possible by the recent development of the methodology and improvement in the accuracy of an automated high-throughput screening system. In this study, we screened natural product libraries to detect compounds with anticancer effects using HeLa cells. Of the 420 plant extracts screened, the extract of Angelica gigas Nakai (AGN) was the most effective in reducing cell viability of HeLa cells. Markers of apoptosis, such as exposure of phosphatidylserine and cleavage of caspase-7 and PARP, were increased by treatment with the AGN extract. Treatment of the AGN extract increased expression of PKR as well as ATF4 and CHOP, the unfolded protein response genes. In addition, cotreatment of doxorubicin and the AGN extract significantly increased doxorubicin-induced apoptosis in HeLa cells. Decursin and decursinol angelate, which were known to have anticancer effects, were the main components of the AGN extract. These results suggest that the extract of AGN containing, decursin and decursinol angelate, increases doxorubicin susceptibility.